2012
DOI: 10.1590/s0103-84782012000700025
|View full text |Cite
|
Sign up to set email alerts
|

Criação intensiva de suínos em confinamento ou ao ar livre: estudo meta-analítico do desempenho zootécnico nas fases de crescimento e terminação e avaliação de carcaça e carne no Longissimus dorsi

Abstract: ICriação intensiva de suínos em confinamento ou ao ar livre: estudo meta-analítico do desempenho zootécnico nas fases de crescimento e terminação e avaliação de carcaça e carne no Longissimus dorsiIntensive pig production in confinement or outdoor systems: A meta-analytical study of the production performance in the growing and finishing phases and carcass and meat evaluation from the Longissimus dorsi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(11 reference statements)
0
1
0
6
Order By: Relevance
“…In the present study, the animals were slaughtered at lower LW (120 kg), with maximum FCR in finishing phase of 3.92 kg/kg and 4.15 kg/kg for hoop barn and barn, respectively. On the other hand, Demori et al (2012) in a meta-analysis study concluded that the outdoor productive system reduced the ADG of pigs by around 2% and increased the FCR by 3% compared to the classic intensive system. Millet et al (2005) and Lebret et al (2008) explained that the negative interferences observed in the performance of the unconfined pigs are related to the higher energy expenditure of the animals raised in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the animals were slaughtered at lower LW (120 kg), with maximum FCR in finishing phase of 3.92 kg/kg and 4.15 kg/kg for hoop barn and barn, respectively. On the other hand, Demori et al (2012) in a meta-analysis study concluded that the outdoor productive system reduced the ADG of pigs by around 2% and increased the FCR by 3% compared to the classic intensive system. Millet et al (2005) and Lebret et al (2008) explained that the negative interferences observed in the performance of the unconfined pigs are related to the higher energy expenditure of the animals raised in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Após meta-análise sobre a criação intensiva de suínos em confinamento ou ao ar livre, Demoril et al (2012) constataram que os suínos criados em sistemas ao ar livre apresentaram maior consumo diário de ração (9%), ganho de peso inferior (2%) e pior conversão alimentar (3%) quando comparados aos animais criados no sistema confinado. Entretanto, as condições de ambiência oferecidas no primeiro sistema permitem a agregação de valor aos produtos gerados em função do apelo ao bem-estar por parte da sociedade.…”
Section: Fundamentação Teóricaunclassified
“…Embora os índices produtivos como conversão alimentar, ganho de peso e consumo de alimentos tenham sido piores no sistema ao ar livre, outros índices como rendimento de carcaça, percentual de carne magra, espessura de toucinho, características de dureza, maciez e suculência da carne não foram influenciadas pelo sistema de criação (DEMORIL et al, 2012). Em relação à mortalidade Carvalho et al (2011) encontraram índices de 6% para maternidade e 2% para creche no sistema SISCON, enquanto no SISCAL a mortalidade foi de 1% nas duas fases.…”
Section: Fundamentação Teóricaunclassified